Method improve performance kvaziparalelnyh homogeneous structures integrating digital - Жабин, В. И.; Ковалев, Н. А. (Problems of Informatization and Control, 2007)
Shown possibility of the speedup of the processes integration in digital integrating machine to account of the reduction of the number step due to use the surplus systems of the numeration(reckoning) with big base